Comparative Study between Bupivacaine with Dexmedetemidine and Bupivacaine with Fentanyl for Caudal Epidural Analgesia Perioperatively in Paediatric Infraumbilical Surgery (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Caudal epidural analgesia is a widely used technique to provide intraoperative and postoperative pain relief in paediatric patients undergoing infra-umbilical surgeries. However, a single-dose caudal block with local anaesthetic alone offers only a limited duration of analgesia. To address this, various adjuvants have been combined with local anesthetics to extend analgesic Effects. Although opioids are commonly used as adjuvants, their use is associated with significant adverse Effects, notably respiratory depression. Objective: To compare the efficacy and safety of dexmedetomidine versus fentanyl as adjuvants to bupivacaine in caudal epidural analgesia for paediatric infra-umbilical surgeries.Methods: A total of 45 children (aged 2–7 years, ASA I–II) undergoing elective infra-umbilical surgeries were randomly assigned to two groups of 25 each. Following anaesthesia induction, Group F received 0.25% bupivacaine (0.75 ml/kg) with fentanyl (2 μg/kg) while Group D received 0.25% bupivacaine (0.75 ml/kg) with dexmedetomidine (2 μg/kg) via caudal block. Hemodynamic parameters were monitored regularly. Postoperative pain and sedation were assessed using the FLACC and Ramsay scales, respectively. Time to first rescue analgesia, total 24-hour analgesic use and perioperative complications over six hours were documented.Results: Both paediatric groups (Group F and Group D, n=45) were comparable in demographics, ASA class, surgery type, and anaesthesia duration (p>0.05). Surgical indications were similarly distributed (p=0.762). Heart rate and blood pressures were initially similar but significantly lower in Group D after 10–20 minutes (p